FACTORS INFLUENCING EXCHANGE STRUCTURE CHANGES IN ADAPTATION FROM NOVEL TO FILM OF R.J. PALACIO’S WONDER - Salasati, Maida; Garnida, Susie Chrismalia (Anaphora : Journal of Language, Literary, and Cultural Studies, 2021)
This article reports a study on conversational aspects of adaptation from novel to movie. Specifically it reports the exchange structure changes when dialogues in novel is adapted into movie, the issue of fidelity that is involved in the changes, and how the changes affect information or message of the original exchange. This study adopts Stam’s (2000) theory on adaptation and MacCarthy’s (1991) theory on exchange structure of conversation to analyze R.J. Palacio’s novel Wonder (2012) and its film adaptation with the same title Wonder (2017). This descriptive qualitative study involves 9 data selected from the conversations of the main character, Auggie, in the novel and their corresponding dialogues in the film. The finding shows that the changes of structure elements is influenced by the changes of settings and participants, as well as the need of focus and emphasis of given issues in the conversation.